Praktik Moderasi Beragama melalui Seni Macapat dalam Peningkatkan Ekonomi Anggota - Sumarjoko Sumarjoko; Khamim Saifuddin; Tri Wulantoro; Yauma Ida Fitria; Mahdee Maduerawae (Amorti: Jurnal Studi Islam Interdisipliner, 2023)
This study reveals the phenomenon of the people of Kembang village, Nanggulan sub-district who make the macapat art tradition a medium of religious moderation and economic improfment its members. This theme is considered important considering the erosion of religious tolerance in society due to the rise of claims, stereotypes and blasphemy of religion. This is a field research with a case study approach. The results of the research concluded that: 1) the macapat tradition is the only art favored by Muslims and Catholics in the Nanggulan sub-district so that it is used as a medium of religious moderation, 2) the existence of the Anggoro Kasih community is the main patron who contributes to religious moderation through macapat performances with songs which breathes harmony, mutual cooperation and mutual respect between religious communities.